Issues influencing staff turnover in government and the effects Act 10 has on correctional employees - Williams, James M. (My University, 2014)
In this project I will research, analyze and summarize previous studies completed on staff turnover amongst government employees. I will then develop a Survey and distribute it to state employees utilizing a small sample set of correctional employees for the State of Wisconsin. The survey and its questions were designed to evaluate the effect Act 10 and its components have on an employee's thoughts and feelings about their current work status. It was also designed to study the effect it has on their motivation to continue with their current career, seek a different career within government and/or switch careers and leaving government employment all together. I will compare the survey responses from state employees with the information collected from past literature studies. The results will help support my hypothesis that the Act 10 Legislation was more effective in increasing staff turnover than it was at influencing staff retention.
A Field Project Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Public Administration Healthcare Management
Keywords: Work environment; Quality of work life; Job stress; Corectional personnel - Wisconsin; Labor disputes; Labor turnover; Collective bargaining - correctional institutions - Wisconsin